Respuesta :

caylus
Hello,

x²-5x-36=x²-9x+4x-36
=x(x-9)+4(x-9)
=(x-9)(x+4)

The factorized form is (x-9)(x+4).

x²-5x-36=x²-9x+4x-36

=x(x-9)+4(x-9)

=(x-9)(x+4)

What is factorized form?

Factored form, the made from a constant and two linear phrases. The parameters are the roots of the characteristic (the x-intercepts of the graph ). Changing a quadratic characteristic to factored shape is called factoring.

A quadratic expression this is written because the fabricated from a constant times linear factors is stated to be in factored shape. as an instance, and are both in factored form. the same old form of a quadratic expression in is , wherein , , and are constants, and is not 0.

Learn more about polynomial here: https://brainly.com/question/2833285

#SPJ2